Large oncosomes contain distinct protein cargo and represent a separate functional class of tumor-derived extracellular vesicles - Minciacchi, Valentina R.; You, Sungyong; Spinelli, Cristiana; Morley, Samantha; Zandian, Mandana; Aspuria, Paul-Joseph; Cavallini, Lorenzo; Ciardiello, Chiara; Sobreiro, Mariana Reis; Morello, Matteo; Kharmate, Geetanjali; Jang, Su Chul; et al. (Oncotarget, 2015)
Large oncosomes (LO) are atypically large (1-10 µm diameter) cancer-derived extracellular vesicles (EVs), originating from the shedding of membrane blebs and associated with advanced disease. We report that 25% of the proteins, identified by a quantitative proteomics analysis, are differentially represented in large and nano-sized EVs from prostate cancer cells. Proteins enriched in large EVs included enzymes involved in glucose, glutamine and amino acid metabolism, all metabolic processes relevant to cancer. Glutamine metabolism was altered in cancer cells exposed to large EVs, an effect that was not observed upon treatment with exosomes. Large EVs exhibited discrete buoyant densities in iodixanol (OptiPrep(TM)) gradients. Fluorescent microscopy of large EVs revealed an appearance consistent with LO morphology, indicating that these structures can be categorized as LO. Among the proteins enriched in LO, cytokeratin 18 (CK18) was one of the most abundant (within the top 5th percentile) and was used to develop an assay to detect LO in the circulation and tissues of mice and patients with prostate cancer. These observations indicate that LO represent a discrete EV type that may play a distinct role in tumor progression and that may be a source of cancer-specific markers.